2007
DOI: 10.1016/j.neuroscience.2006.09.053
|View full text |Cite
|
Sign up to set email alerts
|

Two types of neurotransmitter release patterns in isolectin B4-positive and negative trigeminal ganglion neurons

Abstract: Mammalian nociceptors have been classified into subclasses based on differential neurotrophin sensitivity and binding of the plant isolectin B4 (IB4). Most of the nerve growth factor-responsive IB4-negative (IB4 (-)) nociceptors contain neuropeptides such as substance P and calcitonin gene-related peptide, whereas the glial-derived neurotrophic factor-responsive IB4-positive (IB4 (+)) neurons predominantly lack such neuropeptides. We hypothesized that the differences in neuropeptide content between IB4 (+) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 82 publications
(103 reference statements)
1
14
0
Order By: Relevance
“…For these reasons, we suggest that the stimulus-evoked release of CGRP occurs in a calcium-dependant manner from areas of LDCV exocytosis in a regulated fashion. This is consistent with electron microscopy studies (Alvarez et al, 1993;Hayes and Carlton, 1992) and functional investigations in the literature (Hingtgen and Vasko, 1994a;Kitamura et al, 2009;Matsuka et al, 2007). Because synaptic vesicles and LDCVs share similarities in the core aspects of the machinery involved in transmitter release (Edwards, 1998), our results showing the synaptic localization of CRMP-2 suggests that a CRMP-2-mediated increase in neurosecretion might occur via both classical and non-classical mechanisms.…”
Section: Crmp-2 Modulates Transmitter Releasesupporting
confidence: 92%
See 1 more Smart Citation
“…For these reasons, we suggest that the stimulus-evoked release of CGRP occurs in a calcium-dependant manner from areas of LDCV exocytosis in a regulated fashion. This is consistent with electron microscopy studies (Alvarez et al, 1993;Hayes and Carlton, 1992) and functional investigations in the literature (Hingtgen and Vasko, 1994a;Kitamura et al, 2009;Matsuka et al, 2007). Because synaptic vesicles and LDCVs share similarities in the core aspects of the machinery involved in transmitter release (Edwards, 1998), our results showing the synaptic localization of CRMP-2 suggests that a CRMP-2-mediated increase in neurosecretion might occur via both classical and non-classical mechanisms.…”
Section: Crmp-2 Modulates Transmitter Releasesupporting
confidence: 92%
“…Whereas SVs might be located at a distance of 20 nm from the calcium channel, LDCVs might reside as far as 300 nm away from the channels (Park and Kim, 2009), a spatial separation suggestive of differences in the calcium-dependence of release. However, FM4-64 has been used to examine cycling of LDCVs in trigeminal ganglia, in which CGRP is a major peptide transmitter and where the physiology is similar to the DRG (Matsuka et al, 2007). In addition, the stimulus-evoked release of CGRP from isolated sensory neurons occurs in a calciumdependent manner (Hingtgen and Vasko, 1994a).…”
Section: Crmp-2 Modulates Transmitter Releasementioning
confidence: 99%
“…In Figure 2B, the vesicle membrane is shown by red fluorescence, while the nuclei are shown by blue fluorescence. Many ring-like structures of red fluorescence clustering together around the cell's margin (see the white arrows) are believed to be the large vesicles according to previous reports (Matsuka et al, 2007;Vida and Emr, 1995). The small and unattached vesicles may present a dot-like morphology in the cytoplasm (see the white cycle region) due to the resolution limit of optical microscopy.…”
Section: Simultaneously Afm Imaging and Fluorescentmentioning
confidence: 71%
“…These data suggested that IB4(þ) TG neurons have faster exocytosis and endocytosis than IB4(À ) neurons [16].…”
Section: Introductionmentioning
confidence: 85%